Glazbeni pisac Vjenceslav Novak - Majer-Bobetko, Sanja (2020)
Vjenceslav Novak hrvatskoj je kulturnoj javnost uglavnom znan kao književnik. Manje je poznato da je bio jedan od rijetkih hrvatskih glazbenika sa završenim formalnim visokim glazbenim obrazovanjem te je egzistenciju sebi i obitelji osiguravao kao profesor različitih glazbenih predmeta. Usto je od 1888. godine petnaestak godina objavljivao brojne članke u periodici i monografska izdanja. Ti radovi razotkrivaju široku lepezu Novakovih profesionalnih zanimanja: od glazbene kritike preko teorije, pedagogije, metodike, organologije i estetike glazbe, do glazbene historiografije, što ga, uz utemeljitelja hrvatske muzikologije uopće, Franju Ksavera Kuhača, čini vodećim glazbenim piscem s prijeloma 19. i 20. stoljeća.
Vjenceslav Novak (1859 – 1905) is generally known to the Croatian cultural public as a writer. It is less well-known that he was one of the few Croatian musicians with an excellent formal higher education in music. In 1886 he acquired the title of organist at the Prague Conservatory, and in 1887 he was a teacher of singing and music theory. Therefore, he was able to provide for himself and his family as a professor of various musical subjects in the Male Teacher-Training School and the school of the Croatian Music Institute in Zagreb. Along with this, from 1888 he published numerous articles in periodicals and monographs for 15 years. These works reveal the wide range of Novak’s professional interests: from musical criticism via theory, pedagogy, methodology, organology and the aesthetics of music, to musical historiography, which, along with the founder of Croatian musicology in general, Franjo Ksaver Kuhač (1834-1911), makes him a leading writer of music from the turn of the 19th into the 20th century. His first works belong to the field of musical pedagogy and music criticism. He was the author of the first textbooks about the harmony in the Croatian language (1889, 1890 and 1898), Upute u orguljanje (How to play the organ) (1893), intended for teaching organ playing and numerous other works, in which he talks about various themes, from the most general views of music schooling and questions in relation to music and education, where he also touches upon the musical-social problematics of the unsatisfactory social position of music and musicians, to training in singing, which includes the problem of children’s health, voice-breaking, music theory and methodology. Novak’s small number of musical reviews mainly reveal a critic who strives and often manages to explain his views in a reasoned and expert way. From 1889 Novak directed his attention to music historiography.
2. Senjski interdisciplinarni simpozij "Dragi Novače!", Senj, 26.-27.4.2019.
Bibliografske bilješke uz tekst ; bibliografija: str. 56-62.
Sažetak ; Summary.
Keywords: Književnici -- Glazbenici -- Glazbena pedagogija -- Glazbena historiografija -- Povijest glazbe; Novak, Vjenceslav